2013
DOI: 10.1515/mammalia-2012-0063
|View full text |Cite
|
Sign up to set email alerts
|

Lion predation on livestock and native wildlife in Waza National Park, northern Cameroon

Abstract: The feeding ecology of lions (Panthera leo, Linnaeus 1758) was investigated in and around Waza National Park, northern Cameroon. Diet was determined using global positioning system (GPS) data of lion kill sites (clusters of GPS location points) collected using radio collars. Lions consumed 14 different prey species, with five species that were either medium (50–200 kg) or large (>200 kg) in size forming the bulk of kills. The western kob (Kobus kob kob) was the most common (23.5%) wild prey of lions, but wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 27 publications
2
17
0
Order By: Relevance
“…The changes observed in home range size attributed to decreased prey may explain recent increases in the levels of livestock depredation and park degradation. In 2001, Bauer (2003) found that livestock comprised 10% the diet of lions in Waza National Park, which has now increased to 22% (Tumenta et al 2013a). It is also possible that home range might have increased because of reduced competition for the same area as a result of a recent drop in lion population in Waza National Park.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The changes observed in home range size attributed to decreased prey may explain recent increases in the levels of livestock depredation and park degradation. In 2001, Bauer (2003) found that livestock comprised 10% the diet of lions in Waza National Park, which has now increased to 22% (Tumenta et al 2013a). It is also possible that home range might have increased because of reduced competition for the same area as a result of a recent drop in lion population in Waza National Park.…”
Section: Discussionmentioning
confidence: 99%
“…However, locals do not seem to make much effort to solve the problem and attacks do at times result in retaliatory killing (De Iongh et al 2009;Tumenta et al 2010). Nonetheless, when one consider that 22% of the lion's diet nowadays comes from livestock (Tumenta et al 2013a), people do indeed show remarkable levels of tolerance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We recognise that this study unintentionally underrepresents depredation by lions, leopards and cheetahs in Southern and East Africa, where human-felid conflicts over livestock killing are rather frequent (Inskip & Zimmermann 2009, Tumenta et al 2013, Balme et al 2014. This is because the diet of big cats in these regions has been studied from prey kills and not from scats (Hayward et al 2006, Bissett & Bernard 2007, Tambling et al 2012, Tumenta et al 2013. As a result, we used only limited scat-based data from Marker et al (2003) for cheetahs in Namibia and from Braczkowski et al (2012) for leopards in South Africa.…”
Section: Khorozyan Et Al Prey Consumption By Big Catsmentioning
confidence: 99%
“…As ungulates and other prey species have been depleted through human persecution and habitat loss, carnivores increasingly rely on domestic animals to survive (Azevedo 2008, Inskip & Zimmermann 2009, Ripple et al 2014, Khorozyan et al 2015, Ghoddousi et al 2016. Depredation often leads to retaliatory killing of large carnivores by humans, especially of big cats such as the lion Panthera leo, tiger Panthera tigris, jaguar Panthera onca, leopard Panthera pardus, snow leopard Panthera uncia, puma Puma concolor, and cheetah Acinonyx jubatus, which prey on economically valuable livestock and occasionally may attack humans (Inskip & Zimmermann 2009, Marchini & Macdonald 2012, Banerjee et al 2013, Tumenta et al 2013). Due to prey depletion and human persecution, six of the seven big cat species (86%) are classified by the International Union for Conservation of Nature (IUCN; Anonymous 2016) as Near Threatened to Endangered, in spite of their flagship status which stimulates substantial research and conservation efforts worldwide.…”
Section: Introductionmentioning
confidence: 99%